Pengaruh Prestasi Belajar Pada Mata Pelajaran IPS Terhadap Pembentukan Kompetensi Sosial Siswa Kelas VI SD Negeri Se Sulawesi Utara - Sarah S. N. Tombokan (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to determine the effect of learning achievement on social studies subjects with the formation of social competence of students of class VI Public Elementary Schools in North Sulawesi Province, and to find out how the influence of ethnicity in the formation of social competence of students of class VI of State Elementary Schools in North Sulawesi after attending the subjects Social Science lessons. In this study, the data collection methods used were: the questionnaire method (questionnaire): the questionnaire in this study consisted of questions that were used to collect data related to the Social Competence variable. Documentation method is used to retrieve data about learning achievement which can be seen from the value of learning outcomes in the form of values ​​from report cards. Hypothesis test using regression analysis significance test, simple linear, simple correlation, significance test and simple correlation analysis, partial correlation analysis and significance test of partial correlation analysis. This study proves that there is a significant effect of the learning achievement variable on the formation of social competence in grade VI elementary school students based on ethnicity throughout North Sulawesi. The influence of learning achievement on the formation of social competence of sixth grade elementary school students based on ethnicity throughout North Sulawesi is 7.3%. But the effect is significant when the value of learning achievement increases. The sixth grade elementary school students have higher learning achievement in this study. But still in the medium category or the same as other ethnic values. The relationship between learning achievement and the formation of social competence is in the low category.